COMMUNICATION AUDIT MODELS AND ORGANIZATIONAL COMMUNICATION PERFORMANCE: A LITERATURE REVIEW - Nisa Rahmadani; Miftahul Hasanah; Alya Syahla Kamila Irawan (OPINI: Journal of Communication and Social Science, 2026)
Communication is a fundamental element in organizational management that determines operational effectiveness and goal achievement. However, many organizations do not yet have a systematic communication evaluation system. This study aims to examine the application of communication audit models to improving organizational communication performance through a literature study approach. The method used is library research with descriptive-analytical analysis techniques and literature synthesis from national and international scientific journal sources, textbooks, and proceedings published between 2000 and 2024. The results of the study show that communication audit models such as the ICA Communication Audit, Communication Satisfaction Questionnaire (CSQ), and Organizational Communication Profile (OCP) significantly contribute to identifying weaknesses in internal communication, improving the communication climate, and measuring the communication satisfaction of organizational members. Periodic application of communication audits has been proven to increase the effectiveness of two-way communication, strengthen cross-divisional coordination, and promote employee engagement. This study concludes that a communication audit is not only a diagnostic tool, but also a strategic instrument for improving organizational performance on an ongoing basis.